A Just and Righteous Cause : Benjamin H. Grierson's Civil War Memoir - Grierson, Benjamin Henry, 1826-1911 (Book collections on Project MUSE., 2008)
General Benjamin H. Grierson is most widely known as the brilliant cavalryman whose actions in the Civil War's Mississippi Valley campaign facilitated Ulysses S. Grant's capture of Vicksburg. There is, however, much more to this key Union officer than a successful raid into Confederate-held Mississippi. In A Just and Righteous Cause: Benjamin H. Grierson's Civil War Memoir, edited by Bruce J. Dinges and Shirley A. Leckie, Grierson tells his story in forceful, direct, and highly engaging prose. A Just and Righteous Cause paints a vivid picture of Grierso.